Effect of plasmochemically activated aqueous solution on process of food sprouts production - Pivovarov, Oleksandr; Півоваров, Олександр; Kovaliova, Olena; Ковальова, Олена; Koshulko, Vitalii; Кошулько, Віталій (National University of Food Technologies, 2020)
The effect of plasmochemically activated aqueous solutions on the process of production of food sprouts of legume crops is studied. The paper presents the characteristic of activated aqueous solutions, their effect on the germination process and microbiological status of sprouts. Materials and methods. Grain of legumes (peas, soybeans, chickpeas, kidney beans, lentils, beans, lupines) was sprouted with the use of plasmochemically activated aqueous solutions as an intensifier of germination. In order to determine the amino acid and vitamin composition of sprouts, the method of ion-exchange liquid column chromatography was used. Results and discussion. Legume germination energy and capacity increased with the use of plasmochemically activated aqueous solutions. At the optimal concentration of peroxides equal to 400 mg/l, the germination energy increased by 10–12%, and the germination capacity featured growth by 8–10%. Monitoring of the sprout length showed the increase in length from 6 to 14 mm. Control of weight of sprout biomass also demonstrated positive results, that is, 4–16 % sprout weight gain, depending on the crop (peas ̶8%; soybeans ̶10%; chickpeas ̶ 7%; kidney beans ̶14%; lentils ̶ 4%; beans ̶ 16%; lupines ̶ 10%). Study of the microbiological status of sprouts showed stable disinfecting action of plasmochemically activated aqueous solutions owing to the presence of hydrogen peroxide in their composition (100–700 mg/l). No pathogenic microflora was recorded on the sprouts treated with plasmochemically activated aqueous solutions with the peroxide concentration of 400 mg/l and more (Aspergillus, Alternaria, Penicillium, Fusarium, Mucor). Owing to the usage of plasmochemically activated aqueous solutions, legume sprouts demonstrated the increase in the content of B group vitamins (В1, В2, В3, В6, В12), as well as РР, Е, С, А. The number of amino acids increased by 4–52%. It is explained by more active development of legume sprouts, while using the intensifier of germination, i.e. plasmochemically activated aqueous solutions. Conclusions. Usage of plasmochemically activated aqueous solutions is a promising process technology for obtaining highquality product rich in amino acids and vitamins. Досліджено вплив плазмохімічно активованих водних розчинів на процес виробництва харчових паростків зернобобових культур. У статті представлена характеристика активованих водних розчинів, їх вплив на процес проростання та мікробіологічний статус паростків. Матеріали та методи. Зерно бобових (горох, соя, нут, квасоля, сочевиця, квасоля, люпин) пророщували із застосуванням плазмохімічно активованих водних розчинів як інтенсифікатора проростання. Для визначення амінокислотного та вітамінного складу паростків застосовували метод іонообмінної рідинної колонкової хроматографії. Результати і обговорення. Енергія проростання бобових культур і здатність зростала із застосуванням плазмохімічно активованих водних розчинів. При оптимальній концентрації пероксидів, що дорівнює 400 мг / л, енергія проростання зросла на 10–12%, а здатність до проростання зросла на 8–10%. Моніторинг довжини паростка показав збільшення довжини з 6 до 14 мм. Контроль ваги біомаси паростків також продемонстрував позитивні результати, тобто 4–16% приросту маси паростка залежно від урожаю (горох - 8%; соя - 10%; нут - 7%; квасоля - 14%; сочевиця - 4%; квасоля ̶ 16%; люпин ̶ 10%). Вивчення мікробіологічного статусу паростків показало стабільну дезінфікуючу дію плазмохімічно активованих водних розчинів завдяки наявності в їх складі перекису водню (100–700 мг / л). Не виявлено патогенної мікрофлори на паростках, оброблених плазмохімічно активованими водними розчинами з концентрацією перекису 400 мг / л і більше (Aspergillus, Alternaria, Penicillium, Fusarium, Mucor). Завдяки використанню плазмохімічно активованих водних розчинів паростки бобових культур продемонстрували збільшення вмісту вітамінів групи В (В1, В2, В3, В6, В12), а також РР, Е, С, А. Кількість амінокислот зросла на 4–52%. Це пояснюється більш активним розвитком паростків бобових, використовуючи при цьому інтенсифікатор проростання, тобто плазмохімічно активовані водні розчини. Висновки. Використання плазмохімічно активованих водних розчинів - перспективна технологія отримання високоякісного продукту, багатого амінокислотами та вітамінами.
Вплив плазмохімічно активованого водного розчину на процес виробництва харчових паростків
Keywords: Sprouts; паростки; Activation; активація; Intensifier; підсилювач; Germination; схожість; Legumes; бобові культури